Effect of health insurance on delivery care utilization and perceived delays and barriers among southern Thai women - Oumudee Nurlisa; Liabsuetrakul Tippawan (BMC, 2011)
Abstract Background Financial reform aims to overcome the problems of financial barriers and utilization of health services. However, it is unclear whether financial reforms or health insurance can reduce delays and/or barriers or if there are still other important obstacles for preventing pregnant women accessing delivery care. This study aimed to assess the effect of health insurance and other factors on delivery care utilization and the perception of delays and barriers to delivery care among women living in Songkhla province, Thailand. Methods A cross-sectional study was conducted from November 2007 to December 2008. Women who delivered at hospital or home in the areas of participating hospitals in four districts were interviewed at 24- or 48-hours postpartum. The impact of health insurance and other factors on outcomes of interest was assessed using multivariate logistic regression. Results Of 2,847 women, 2,822 delivered at a hospital and 25 at home, of which 80% and 40% had health insurance for delivery care, respectively. Muslims, low educated women, those who thought they could not use health insurance for delivery care and those less willing to seek care at their delivery place were more likely to give birth at home. Perception of delays to seeking care, reaching a hospital and receiving care was reduced in women insured by civil servant medical benefit. Women insured by universal coverage and social security perceived a lower delay in reaching a hospital but a higher delay in receiving care. Low education, unwillingness to seek care, out-of-pocket payment, worry about cost of delivery care, transportation difficulties, low perception of receiving good care or a perception of being treated badly were also associated with delays and barriers to health care. Almost all (93%) agreed that health insurance could reduce financial barriers for accessing services. However, having health insurance influenced them to seek care, reach a hospital, and receive care quickly in 50%, 32%, and 23% of the women, respectively. Conclusions Health insurance has a significant impact on perceived delays and barriers, but not place of delivery. Socio-economic determinants continue to play an important role for place of delivery and perceived delays and barriers.